2021
DOI: 10.1186/s12886-020-01749-7
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of lower eyelid epiblepharon and its association with refractive errors in Chinese preschool children: a cross-sectional study

Abstract: Background To assess the prevalence and demographics of lower eyelid epiblepharon in Chinese preschool children and to evaluate its association with refractive errors. Methods In this population-based, cross-sectional study, a total of 3170 children aged 3 to 6 years from Beijing, China underwent examinations including weight, height, cycloplegic autorefraction and slit-lamp examination of external eyes. The prevalence of lower eyelid epiblepharon … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The result of our study was in line with the study conducted by Oshima et al who reported that epiblepharon was more prevalent in Japanese boys than in girls [26]. A cross-sectional study conducted by Zhou et al also showed that young boys had a higher risk of developing epiblepharon than young girls among Chinese preschoolers aged 3-6 years [27].…”
Section: Discussionsupporting
confidence: 92%
“…The result of our study was in line with the study conducted by Oshima et al who reported that epiblepharon was more prevalent in Japanese boys than in girls [26]. A cross-sectional study conducted by Zhou et al also showed that young boys had a higher risk of developing epiblepharon than young girls among Chinese preschoolers aged 3-6 years [27].…”
Section: Discussionsupporting
confidence: 92%
“…(26) A crosssectional study conducted by Zhou et al also showed that young boys had a higher risk of developing epiblepharon than young girls among Chinese preschoolers aged 3-6 years. (27) Different moderation effects of obesity on epiblepharon were observed in the current study. A higher risk of developing epiblepharon among overweight and obese children was encountered in boys aged 4-9 years (OR = 1.74, 95% CI = 1.07-2.82, P = 0.025; OR = 3.06, 95% CI = 1.56-6.03, P = 0.001), and in girls aged 13-18 years (OR = 3.70, 95% CI = 1.38-9.97, P = 0.01).…”
Section: Discussionmentioning
confidence: 44%
“…Recent research shows that Chinese preschool children with lower eyelid epiblepharon have a higher risk of developing astigmatism than those without epiblepharon [ 22 ]. In our study, astigmatism > 1.25 D was found in 87/106 (82.2%) eyes.…”
Section: Discussionmentioning
confidence: 99%